Diseño de una ruta turística MTB (mountain biking) en la parroquia de Aláquez cantón Latacunga provincia de Cotopaxi. - Toscano Izurieta, Mauricio Josué (2018)
Alaquez Parish is located in Latacunga - Cotopaxi Province and it has several natural and cultural attractions with a profitable geographical location for tourism development. That is why this project aims to take advantage of these resources through the design of a tourist route of Mountain biking (MTB); it was taken up with a brief diagnosis of the study area where the social, cultural, economic and environmental factors were identified. Seven tourist attractions were identified with the MINTUR 2017 methodology which are: four natural and three cultural, among natural attractions we have Morro Hill, San Antonio de Aláquez Cooperative, Morro Pansachi Farm and the moors of Tejar Miraflores Association, among the cultural attractions we have Chapel of “San Antonio de Alaquez” , Chapel of Cuchitingue and festivities of “Nuestro Señor de la Misericordia” , and finally the traditional festivitiesof “San Antonio de Padua”, the information obtained was systematized and analyzed for the design of the tourist routes in MTB. It was determined the design of two routes the first route Latacunga-Morro-Latacunga, the second is the route North-East - South of Alaquez there routes are seeking to promote tourism by the bike tour around the different attractions in the parish, through field trips and using applications such as: Wikiloc, Strava, was obtained information for the characterization of the routes, it was used the methodology of characterization of cycle tourism routes of the Guayas, where three factors were determined, the type of management that the routes will have, the ascent or altitudinal ranges and the type of route depending on the distance. The type of terrain was established, such as asphalt, cobbled stones, stony path and dirt track with points of interest on each of the routes.